Clinical Efficacy of Immune Checkpoint Inhibitors in Older Non-small-Cell Lung Cancer Patients: A Meta-Analysis - Sun, You-Meng; Wang, Ying; Sun, Xin-Xing; Chen, Jing; Gong, Zhi-Ping; Meng, Hai-Yan (Frontiers in Oncology, 2020)
Background Immune checkpoint inhibitors (ICIs) have transformed the treatment landscape among non-small-cell lung cancer (NSCLC) patients. The efficacy of ICI therapy in older patients (≥65 years) is controversial and not fully clarified. We performed a systematic review and meta-analysis to evaluate the efficacy of ICIs in patients with advanced or metastatic NSCLC based on age (＜65 years vs ≥65 years). Methods A comprehensive literature search for eligible randomized control phase II/III trials that compared the efficacy of anti-PD-1/PD-L1 agents against chemotherapy in advanced or metastatic NSCLC patients. Pooled overall survival (OS) and progression-free survival (PFS) estimates were calculated based on random/fixed-effects models according to the heterogeneity between the studies. Results A total of 10 studies involving 8 randomized controlled trials (2 updates) were enrolled in this meta-analysis [2662 young patients (＜65 years) and 1971 older patients (≥65 years) ]. The efﬁcacy of anti-PD-1/PD-L1 agents is comparable between young (＜65 years) and older (≥65 years) patients for OS [HR 0.75 95% CI (0.64–0.88) vs. 0.76 95% CI (0.66–0.87)]. However, our pooled analysis was not sufficient to show a significant benefit in terms of PFS for anti-PD-1/PD-L1 agents [HR 0.87 95% CI (0.74–1.01), P=0.06]. In addition, we failed to see a PFS superiority of anti-PD-1/PD-L1 agents against chemotherapy in two age subgroups [＜65 years and ≥65 years, HR 0.85 95% CI (0.72–1.01), P=0.07 and HR 0.87 95% CI (0.68–1.10), P=0.25]. Conclusion ICIs therapy presents comparable efficacy in older advanced or metastatic NSCLC patients with young patients.